Catheter-Based Therapies Decrease Mortality in Patients With Intermediate and High-Risk Pulmonary Embolism: Evidence From Meta-Analysis of 65,589 Patients - Arkadiusz Pietrasik; Aleksandra Gąsecka; Łukasz Szarpak; Łukasz Szarpak; Michał Pruc; Tomasz Kopiec; Szymon Darocha; Marta Banaszkiewicz; Maciej Niewada; Marcin Grabowski; Marcin Kurzyna (Frontiers in Cardiovascular Medicine, 2022)
BackgroundCatheter-directed therapies (CDT) are an alternative to systemic thrombolysis (ST) in pulmonary embolism (PE) patients, but the mortality benefit of CDT is unclear.ObjectiveWe conducted a systematic review with meta-analysis to compare the efficacy and safety of CDT and ST in intermediate-high and high-risk PE.MethodsWe included (P) participants, adult PE patients; (I) intervention, CDT; (C) comparison, ST; (O) outcomes, mortality, complications, in-hospital treatment, and length of hospital stay; (S) study design, randomized controlled trials (RCTs), or cohort comparing CDT and ST. The primary endpoint was 30-day mortality. Secondary outcomes included treatment-related complications including bleeding, the use of hospital resources, and length of hospital stay.ResultsEleven studies including 65,589 patients met the inclusion criteria. Thirty-day mortality was lower in the CDT group, compared to ST group [7.3 vs. 13.6%; odds ratio (OR) = 0.51, 95% confidence interval (CI) 0.38–0.69, p < 0.001]. The rates of myocardial injury, cardiac arrest, and stroke were lower in CDT group, compared to ST group (p < 0.001 for all). The rates of any major bleeding, intracranial hemorrhage, hemoptysis, and red blood cell transfusion were lower in patients treated with CDT, compared to ST (p ≤ 0.01 for all). Extracorporeal life support was used more often in patients treated with CDT, compared to ST (0.5 vs. 0.2%, OR = 2.52, 95% CI 1.88–3.39, p < 0.001). The use of hospital resources and length of hospital stay were comparable in both groups.ConclusionCDT might decrease mortality in patients with intermediate-high and high-risk PE and were associated with fewer complications, including major bleeding.